Peta Mata Pelajaran Agama Dalam Pendidikan Nasional - Ahmad Darlis; Ahmad Ridho; Adhelia Ferari ; Mhd Rifqih Fernanda; Rizka Ardiyanti (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
Everyone should pursue their education. The nation will also grow through education. In Indonesian education, the term "Islamic Religious Education" refers to a number of subjects including: the Qur'an, hadith, morals, jurisprudence, and the history of Islamic culture. At the Elementary and Secondary Education Levels, subjects related to Islamic Religious Education are taught and studied in clusters. The empirical paradigm of science dominates the implementation curriculum in student education and teaching. Philosophical standards that are contextual and otherworldly in nature that are supralogically dynamic are not too dominant in Islamic education and teaching in schools, considering that the level of improvement and scientific strength of students is not yet fully developed. Keywords: Map of Religious Subjects in Islamic Education